ON THE USE OF DISCRETE FOURIER TRANSFORM FOR SOLVING BIPERIODIC BOUNDARY VALUE PROBLEM OF BIHARMONIC EQUATION IN THE UNIT RECTANGLE - A. D. GARNADI (MILANG Journal of Mathematics and Its Applications, 2003)
This note is addressed to solving biperiodic boundary value problem of biharmonic equation in the unit rectangle. First, we describe the necessary tools, which is discrete Fourier trans- form for one dimensional periodic sequence, and then extended the results to 2-dimensional biperiodic sequence. Next, we use the discrete Fourier transform 2-dimensional biperiodic sequence to solve discretization of the biperiodic boundary value problem of Biharmonic Equation.